The Correlation of Maternal Factors and The Quality of Antenatal Care Services With Low Birth Weight Babies In Health Facilities Level I - Wira Meiriza; Aladin Aladin; Edison Edison (Faculty of Medicine, Universitas Andalas, 2018)
Infant Mortality Rate in West Sumatra still increased from 96 cases in 2015 becomes 111 cases in 2016. One of the contributors to this was the case of Low Birth Weight Babies (LBWB), wich is birth weight < 2500 grams. Causative factors of LBWB are derived from maternal factors because it is related to fetal growth, starting from the moment of conception until the baby is born. Maternal health is very influential towards the growth and development of the fetus. In addition, Antenatal Care is also require to monitor maternal health. Antenatal service care quality can detect the occurrence of risk in pregnancy. This study aims to determine the relationship of maternal factors based on maternal age, parity, distance of pregnancy, complications of pregnancy, economic status, nutritional status, anemia status, antenatal care implementation and the quality of antenatal care services with LBWB incidence on health facilities level 1 in Padang City. This study used a comparative cross-sectional design totalling 72 respondents consisting of a group of mothers who gave birth to babies with birth weight < 2500 grams and ≥ 2500 grams using consecutive sampling technique. Then conducted interviews and observations by using questionnaires as well as data processing were carried out using SPSS. The results showed there was a correlation between pregnancy complications (p = 0.033), anemia status (p = 0.016) and the implementation of antenatal care (p = 0.000) with the incidence of LBWB, while the unrelated were maternal age (p = 0.405), parity (p = 1,000), pregnancy distance (p = 1,000), economic status (p = 0.637), nutritional status (p = 0.326), and quality of antenatal care services (p = 0.812).The conclusion of this study is that there is no correlation between the quality of antenatal care services and the incidence of LBWB, and the implementation of antenatal care is the dominant factor related with the incidence of LBWB in Padang City.